Why nutrient loading reductions alone cannot suppress Cladophora proliferation: insights from a coupled nearshore ecological model - Yasasi Fernando; Lisa Yu; Alexey Neumann; David Depew; Reza Valipour; George B. Arhonditsis (Ecological Modelling, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

An ensemble SPARROW framework for assessing phosphorus export risk and supporting adaptive management in the northern Lake Erie basin - Alexey Neumann; Odai I. Al Balasmeh; Akunne Okoli; George B. Arhonditsis (Journal of Environmental Management, 2026)

Why should models talk to each other? A multipronged modelling strategy as an operational framework to guide adaptive watershed management in the Bay of Quinte Basin, Ontario, Canada - Carlos Alberto Arnillas; Aisha Javed; Alex Neumann; Lamees Shah; George B. Arhonditsis (Ecological Modelling, 2026)

Coupling sedimentary cycling with eutrophication severity under transient external phosphorus and iron loading regimes - Tao Xu; Alex Neumann; Maria Dittrich; Yasasi Fernando; John Gibson; Ramin Farnood; David Depew; George B. Arhonditsis (Ecological Modelling, 2026)

A review on the effects of climate change and pollution on Vibrio infection dynamics - Iraitz Jauregui; Aline Chiabai; Marc B. Neumann (Environmental Impact Assessment Review, 2026)

Initial characterization of M2-muscarinic receptor overexpressing mouse heart - Ulrich Gergs; Igor B. Buchwalow; Britt Hofmann; Jaromir Myslivecek; Katerina Janisova; Katarina Hadova; Franziska Schettler; Max Keller; Jan Klimas; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
There are five muscarinic receptor subtypes expressed in the human heart. The main subtype is the M 2 -muscarinic receptor. We hypothesized that overexpression of the M 2 -muscarinic receptor should augment any contractile effects that are M 2 -muscarinic receptor–mediated. Therefore, we generated a transgenic mouse with overexpression of the human M 2 -muscarinic receptor under the control of the heart-specific α-myosin heavy chain promoter (M 2 -TG). We performed contraction experiments with electrically stimulated (1 Hz) left atrial preparations (LA) and spontaneously beating right atrial preparations (RA) from adult M 2 -TG or from adult wild-type littermate mice (WT). We confirmed the expression of the human M 2 -muscarinic receptor in the mouse heart by reverse transcription polymerase chain reaction (RT-PCR) and radioligand binding experiments at cardiac membranes and tissue sections. We did not detect differences in hematoxylin/eosin staining or Masson/Goldner staining between M 2 -TG and WT. We noticed that carbachol (10 nM–10 µM cumulatively applied) alone or in the presence of 1 µM isoprenaline reduced the force of contraction (FOC) to a similar extent in LA from M 2 -TG and WT. The beating rate in RA was similarly decreased by carbachol alone or by carbachol in the presence of 1 µM isoprenaline in M 2 -TG and WT. Overall, the number of RA that displayed absolute arrhythmias was higher in atria from M 2 -TG compared to atria from WT. No arrhythmias were noted in LA from M 2 -TG or WT. Stimulation of human M 2 -muscarinic receptors induced absolute atrial arrhythmias more often in RA from M 2 -TG than in RA from WT. Overexpressed M 2 -muscarinic receptors were silent to the force and beating rate.

Positive inotropic effects of glucose-dependent insulinotropic polypeptide in the human atrium and the mouse atrium - J. Neumann; B. Hofmann; U. Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Glucose-dependent insulinotropic polypeptide formerly called gastrin inhibitory peptide (GIP), a peptide composed of 42 amino acids, is formed in duodenal and jejunal cells. GIP acts via GIP receptors (GIPR). GIPR can stimulate adenylyl cyclases (AC) and increase intracellular cyclic adenosine-3´,5´-monophosphate (cAMP) levels. The physiological role of GIPR in the human heart is not fully understood. Thence, force of contraction (FOC) was studied in isolated electrically driven (1 Hz) human right atrial preparations from patients undergoing bypass surgery due to severe coronary heart disease. We noted that in paced human atrium, GIP increased FOC. This effect was reduced by a GIPR-antagonist (ProGIP). In the presence of 0.1 µM cilostamide, a phosphodiesterase (PDE) 3 inhibitor, the positive inotropic effects (PIE) of GIP were more potent and efficient to raise FOC. Up to 100 nM GIP failed to heighten the spontaneous beating rate in mouse right atrial preparations, but increased FOC in electrically driven left atrial mouse preparations but only in the presence of a PDE 4 inhibitor (100 nM rolipram). We conclude that the human atrium and the mouse atrium contain functional GIPR with respect to FOC.

Geodynamic evolution of the first basaltic volcanism (B1) in the Oslo Rift (Southeast Norway) - Else-Ragnhild Neumann; Sara Callegaro; Stein B. Jacobsen; Eugenia Hyung; Henrik H. Svensen; Bjørn Tore Larsen; Zachary T. Eriksen (Lithos, 2025)

Characterization of biogeochemical cycles in agricultural watersheds: Integrating regional modelling assessment with downstream water quality - Aisha Javed; Ali Saber; Alex Neumann; Carlos Alberto Arnillas; George B. Arhonditsis (Journal of Environmental Management, 2025)

P24-23 Key Agronomic and Safety Characteristics (Key ASCs) and why they matter to improve safety and reduce reliance on animal testing for agricultural solutions - M. Corvaro; M. Battalora; L. Bertomeu; S. Ellis; I. Fegert; J.-C. Garcin; S. Kan-King-Yu; T. Mehta; S. Nadzialek; B. Neumann; P. Rawlinson; U. Rooni; et al. (Toxicology Letters, 2025)

Simulating Carbon Mineralization at Pore Scale in Capillary Networks of Digital Rock - David A. Lazo Vasquez; Jaione Tirapu Azpiroz; Rodrigo Neumann Barros Ferreira; Ronaldo Giro; Manuela Fernandes Blanco Rodriguez; Matheus Esteves Ferreira; Mathias B. Steiner (Transport in Porous Media, 2025)
Predicting the geometrical evolution of the pore space in geological formations due to fluid–solid interactions has applications in reservoir engineering, oil recovery, and geological storage of carbon dioxide. However, modeling frameworks that combine fluid flow with physical and chemical processes at a rock’s pore scale are scarce. Here, we report a method for modeling a rock’s pore space as a network of connected capillaries and to simulate the capillary diameter modifications caused by reactive flow processes. Specifically, we model mineral erosion, deposition, dissolution, and precipitation processes by solving the transport equations iteratively, computing diameter changes within each capillary of the network simultaneously. Our automated modeling framework enables simulations with digital rock samples as large as (1.125 mm) $$^3$$ 3 having 125 $$×$$ × 10 $$^6$$ 6 voxels, within seconds of CPU time per iteration. As an application of the computational method, we have simulated brine injection and calcium carbonate precipitation in sandstone. For quantitatively comparing simulation results obtained with models predicting either a constant or a flow rate-dependent precipitation, we track the time-dependent capillary diameter distribution as well as the permeability of the connected pore space. For validation and reuse, we have made the automated simulation workflow, the reactive flow model library, and the digital rock samples available in public repositories.

Genome-wide association study of Fuchs’ endothelial corneal dystrophy in the German population - Juliane Fechner; Guilherme B. Neumann; Fabia Murza; Leonard Matthias; Marcus Walckling; Claudia Brockmann; Thomas A. Fuchsluger; Tobias Brockmann (Human Genetics, 2025)
The genetic etiology of Fuchs Endothelial Corneal Dystrophy (FECD) is not yet fully elucidated. While the disease is widespread and the leading indication for corneal transplantation in the Western world, the concurrent shortage of corneal transplants underscores the urgent need for further research into the underlying mechanisms. Such investigations could enable the development of innovative therapeutic strategies. Therefore, we aimed to verify candidate genes previously identified and sought after novel variants in the German population. Undertaking a genome wide association study (GWAS) using the Axiom™ Precision Medicine Diversity Array on 157 FECD cases and 309 controls, followed by pathway enrichment analysis, we were able to confirm the significance of the TCF4 locus (rs613872, p = 8.0 × 10 − 23 , OR = 8.60, h 2 = 0.72) and identified a range of novel variants. Further fine-mapping highlighted novel candidate SNPs, such as on chromosome 5 in the SEMA6A gene (rs153643, p = 3.1 × 10 − 9 , OR = 2.75, h 2 = 0.30), and on chromosome 19 in the DNAJC19P3 gene (rs62117964, p = 3.3 × 10 − 8 , OR = 3.61, h 2 = 0.29). SEMA6A gene is involved in apoptotic pathways and cytoskeletal remodeling, making it an interesting candidate gene for further investigations as a potential therapeutic target. Furthermore, several variants were identified in lncRNAs, which presumably influence the expression of nearby protein-coding genes. For example, LOC105372130 , which is associated with corneal hysteresis and corneal resistance factor, may influence the expression of TCF4 .

Arsenic and zinc cycling in Cambodian rice fields of the Tonle Sap floodplain - Yasmine A. Farhat; E-Nieng Muth; Chou Cheythyrith; Lyda Hok; Gordon W. Holtgrieve; Soo-Hyung Kim; Rebecca B. Neumann (Science of The Total Environment, 2025)

Cantharidin and sodium fluoride attenuate the negative inotropic effect of the A1-adenosine receptor agonist N6-(R)-phenylisopropyl adenosine in isolated human atria - R. Schwarz; B. Hofmann; U. Gergs; J. Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Cantharidin and sodium fluoride inhibit the activity of serine/threonine protein phosphatases 1 (PP1) and 2A (PP2A) and increase the force of contraction in human atrial preparations. R-phenylisopropyl adenosine (R-PIA) acts as an agonist at A 1 -adenosine receptors. R-PIA exerts a negative inotropic effect on human atria. The effect of R-PIA—and its various manifestations—are currently explained as a function of the inhibition of sarcolemmal adenylyl cyclase activity and/or opening of sarcolemmal potassium channels. We hypothesise that cantharidin and sodium fluoride may attenuate the negative inotropic effect of R-PIA. During open heart surgery, trabeculae carneae from the right atrium were obtained for human atrial preparations (HAPs). These trabeculae were mounted in organ baths and electrically stimulated at 1 Hz. Furthermore, we studied isolated electrically stimulated left atrial (LA) preparations from female wild-type mice (CD1). The force of contraction was recorded under isometric conditions. R-PIA (1 µM) exerted a rapid negative inotropic effect in the HAPs and mice LA preparations. These negative inotropic effects of R-PIA were attenuated by pre-incubation for 30 min with 100-µM cantharidin in HAPs, but not in mice LA preparations. Adenosine signals via A 1 receptors in a species-specific pathway in mammalian atria. We postulate that R-PIA, at least in part, exerts a negative inotropic effect via activation of serine/threonine phosphatases in the human atrium.

Contractile effects of stimulation of D1-dopamine receptors in the isolated human atrium - U. Gergs; T. H. Pham; L. M. Rayo Abella; C. Hesse; P. Grundig; S. Dhein; B. Hofmann; J. Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Dopamine receptors have been claimed not to directly increase contractility in the human heart. Therefore, we performed contraction experiments in isolated electrically driven human atrial preparations (HAP). For comparison, we performed contraction experiments with left atrial preparations of transgenic mice which harbor a cardiac overexpression of human D 1 -dopamine receptors (D 1 -TG). In D 1 -TG, first we noted that dopamine (10 nM–10 µM cumulatively applied) in the presence of propranolol exerted a concentration- and time-dependent positive inotropic effect in D 1 -TG. In a similar fashion, dopamine increased force of contraction in the presence of 0.4 µM propranolol in HAP and these effects were amplified by pre-treatment with inhibitor of phosphodiesterase III (1 µM) cilostamide. Moreover, contractile effects of dopamine in the presence of propranolol 0.4 µM in HAP were antagonized by odapipam, haloperidol, or raclopride. Ten micromolars of fenoldopam in the presence of cilostamide increased force of contraction in HAP and this effect was antagonized by SCH 23390. We conclude that stimulation of human D 1 -dopamine receptors can increase force of contraction in the HAP.

Phylogenetic characterization of Bifidobacterium kimbladii sp. nov., a novel species from the honey stomach of the honeybee Apis mellifera - M. Modesto; D. Scarafile; A. Vásquez; R. Pukall; M. Neumann-Schaal; S. Pascarelli; B. Sgorbati; M. Ancora; C. Cammà; P. Mattarelli; T.C. Olofsson (Systematic and Applied Microbiology, 2025)

A quantitative modeling framework to understand the physiology of the hypothalamic-pituitary-adrenal axis and interaction with cortisol replacement therapy - Davide Bindellini; Robin Michelet; Linda B. S. Aulin; Johanna Melin; Uta Neumann; Oliver Blankenstein; Wilhelm Huisinga; Martin J. Whitaker; Richard Ross; Charlotte Kloft (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
Congenital adrenal hyperplasia (CAH) is characterized by impaired adrenal cortisol production. Hydrocortisone (synthetic cortisol) is the drug-of-choice for cortisol replacement therapy, aiming to mimic physiological cortisol circadian rhythm. The hypothalamic-pituitary-adrenal (HPA) axis controls cortisol production through the pituitary adrenocorticotropic hormone (ACTH) and feedback mechanisms. The aim of this study was to quantify key mechanisms involved in the HPA axis activity regulation and their interaction with hydrocortisone therapy. Data from 30 healthy volunteers was leveraged: Endogenous ACTH and cortisol concentrations without any intervention as well as cortisol concentrations measured after dexamethasone suppression and single dose administration of (i) 0.5–10 mg hydrocortisone as granules, (ii) 20 mg hydrocortisone as granules and intravenous bolus. A stepwise model development workflow was used: A newly developed model for endogenous ACTH and cortisol was merged with a refined hydrocortisone pharmacokinetic model. The joint model was used to simulate ACTH and cortisol trajectories in CAH patients with varying degrees of enzyme deficiency, with or without hydrocortisone administration, and healthy individuals. Time-dependent ACTH-driven endogenous cortisol production and cortisol-mediated feedback inhibition of ACTH secretion processes were quantified and implemented in the model. Comparison of simulated ACTH and cortisol trajectories between CAH patients and healthy individuals showed the importance of administering hydrocortisone before morning ACTH secretion peak time to suppress ACTH overproduction observed in untreated CAH patients. The developed framework allowed to gain insights on the physiological mechanisms of the HPA axis regulation, its perturbations in CAH and interaction with hydrocortisone administration, paving the way towards cortisol replacement therapy optimization. Graphical Abstract

Studies on the mechanisms of action of MR33317 - Joachim Neumann; C. Hesse; S. Yahiaoui; P. Dallemagne; C. Rochais; B. Hofmann; U. Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
MR33317 was synthesized as an acetylcholinesterase-inhibitor and an agonist at brain 5-HT 4 -receptors. MR33317 might be used to treat Morbus Alzheimer. This therapeutic action of MR33317 might be based on MR33317´s dual synergistic activity. We tested the hypothesis that MR33317 also stimulates 5-HT 4 -receptors in the heart. MR33317 (starting at 10 nM) increased force of contraction and beating rate in isolated atrial preparations from mice with cardiac confined overexpression of the human 5-HT 4 -serotonin receptor (5-HT 4 -TG) but was inactive in wild type mouse hearts (WT). Only in the presence of the phosphodiesterase III-inhibitor cilostamide, MR33317 raised force of contraction under isometric conditions in isolated paced (1 Hz) human right atrial preparations (HAP). This increase in force of contraction in human atrium by MR33317 was attenuated by 10 µM tropisetron or GR125487. These data suggest that MR33317 is an agonist at human 5-HT 4 -serotonin receptors in the human atrium. Clinically, one would predict that MR33317 may lead to atrial fibrillation.

Nitrogen isotope homogenization of dissolved ammonium with depth and 15N enrichment of ammonium during incorporation into expandable layer silicates in organic-rich marine sediment from Guaymas Basin, Gulf of California - Toshiro Yamanaka; Arisa Sakamoto; Kanon Kiyokawa; Jaeguk Jo; Yuji Onishi; Yoshihiro Kuwahara; Ji-Hoon Kim; Lucie C. Pastor; Andreas Teske; Daniel Lizarralde; Tobias W. Höfig; Ivano W. Aiello; et al. (Chemical Geology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Mineralization kinetics of biosiliceous sediments in hot subseafloors - Ivano W. Aiello; Tobias W. Höfig; Armelle Riboulleau; Andreas P. Teske; Daniel Lizarralde; Jeanine L. Ash; Diana P. Bojanova; Martine D. Buatier; Virginia P. Edgcomb; Christophe Y. Galerne; Swanne Gontharet; Verena B. Heuer; et al. (Geochimica et Cosmochimica Acta, 2024)

Healthy environments for athleTes (HEAT): environmental conditions along a 90 km ultra-marathon event, South Africa - H. Havenga; D. Gharbi; N. Sewry; B. Language; F. H. Neumann; J. M. Finch; T. Hill; J. Boulter; E. Jordaan; S. J. Piketh; M. Schwellnus; R. P. Burger (International Journal of Biometeorology, 2024)
This paper provides an overview of the HEAT (Healthy Environments for AthleTes) project, which aims to understand the impact of environmental conditions on athlete health and performance during major sporting events such as long-distance running, cycling, and triathlons. In collaboration with the SAFER (Strategies to reduce Adverse medical events For the ExerciseR) initiative, the HEAT project carried out a field campaign at the 2022 Comrades Marathon in the KwaZulu-Natal province of South Africa. The measurement campaign deployed seven weather stations, seven PM 2.5 monitors and one spore trap along the 90 km route to capture spatially representative measurements of complex micro-climates, allergenic aerospora, and particulate matter exposure. The results indicate that runners were exposed to moderate risk heat stress conditions. Novel findings from this initial campaign shows elevated and potentially harmful PM 2.5 levels at spectator areas, possibly coinciding with small fire events around the race day festivities. Our findings show values PM 2.5 levels over the WHO 24-h guidelines at all stations, while 2000 µg/m 3 at two stations. However, the lack of an acute exposure standard means direct health impacts cannot be quantified in the context of a sport event. The HEAT project highlights important aspects of race day monitoring; regional scale climatology has an impact on the race day conditions, the microclimatic conditions (pollution and meteorology) are not necessarily captured by proximity instruments and direct environmental measurements are required to accurately capture conditions along the route.

Initial characterization of a transgenic mouse with overexpression of the human D1-dopamine receptor in the heart - Lina Maria Rayo Abella; Hannes Jacob; Christin Hesse; Britt Hofmann; Sarah Schneider; Lisa Schindler; Max Keller; Igor B. Buchwalow; CongYu Jin; Pertti Panula; Stefan Dhein; Jan Klimas; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Dopamine can exert effects in the mammalian heart via five different dopamine receptors. There is controversy whether dopamine receptors increase contractility in the human heart. Therefore, we have generated mice that overexpress the human D 1 -dopamine receptor in the heart (D 1 -TG) and hypothesized that dopamine increases force of contraction and beating rate compared to wild-type mice (WT). In D 1 -TG hearts, we ascertained the presence of D 1 -dopamine receptors by autoradiography using [ 3 H]SKF 38393. The mRNA for human D 1 -dopamine receptors was present in D 1 -TG hearts and absent in WT. We detected by in-situ-hybridization mRNA for D 1 -dopamine receptors in atrial and ventricular D 1 -TG cardiomyocytes compared to WT but also in human atrial preparations. We noted that in the presence of 10 µM propranolol (to antagonize β-adrenoceptors), dopamine alone and the D 1 - and D 5 -dopamine receptor agonist SKF 38393 (0.1–10 µM cumulatively applied) exerted concentration- and time-dependent positive inotropic effects and positive chronotropic effects in left or right atrial preparations from D 1 -TG. The positive inotropic effects of SKF 38393 in left atrial preparations from D 1 -TG led to an increased rate of relaxation and accompanied by and probably caused by an augmented phosphorylation state of the inhibitory subunit of troponin. In the presence of 0.4 µM propranolol, 1 µM dopamine could increase left ventricular force of contraction in isolated perfused hearts from D 1 -TG. In this model, we have demonstrated a positive inotropic and chronotropic effect of dopamine. Thus, in principle, the human D 1 -dopamine receptor can couple to contractility in the mammalian heart.

Persistent net release of carbon dioxide and methane from an Alaskan lowland boreal peatland complex - Eugénie S. Euskirchen; Colin W. Edgar; Evan S. Kane; Mark P. Waldrop; Rebecca B. Neumann; Kristen L. Manies; Thomas A. Douglas; Catherine Dieleman; Miriam C. Jones; Merritt R. Turetsky (Global Change Biology, 2024)
Permafrost degradation in peatlands is altering vegetation and soil properties and impacting net carbon storage. We studied four adjacent sites in Alaska with varied permafrost regimes, including a black spruce forest on a peat plateau with permafrost, two collapse scar bogs of different ages formed following thermokarst, and a rich fen without permafrost. Measurements included year‐round eddy covariance estimates of net carbon dioxide (CO 2 ), mid‐April to October methane (CH 4 ) emissions, and environmental variables. From 2011 to 2022, annual rainfall was above the historical average, snow water equivalent increased, and snow‐season duration shortened due to later snow return. Seasonally thawed active layer depths also increased. During this period, all ecosystems acted as slight annual sources of CO 2 (13–59 g C m −2 year −1 ) and stronger sources of CH 4 (11–14 g CH 4 m −2 from ~April to October). The interannual variability of net ecosystem exchange was high, approximately ±100 g C m −2 year −1 , or twice what has been previously reported across other boreal sites. Net CO 2 release was positively related to increased summer rainfall and winter snow water equivalent and later snow return. Controls over CH 4 emissions were related to increased soil moisture and inundation status. The dominant emitter of carbon was the rich fen, which, in addition to being a source of CO 2 , was also the largest CH 4 emitter. These results suggest that the future carbon‐source strength of boreal lowlands in Interior Alaska may be determined by the area occupied by minerotrophic fens, which are expected to become more abundant as permafrost thaw increases hydrologic connectivity. Since our measurements occur within close proximity of each other (≤1 km 2 ), this study also has implications for the spatial scale and data used in benchmarking carbon cycle models and emphasizes the necessity of long‐term measurements to identify carbon cycle process changes in a warming climate.

Thiamethoxam soil contaminations reduce fertility of soil-dwelling beetles, Aethina tumida - Audrey B. Sheridan; Elijah J. Johnson; Armelle Jeannine Vallat-Michel; Gaëtan Glauser; Jeffrey W. Harris; Peter Neumann; Lars Straub (Chemosphere, 2023)

Proline and Silver Nitrate Promotes Multiple Shoot Induction from Mature Embryo and Shoot Tip Explants of Sorghum - B. D. Pawar; N. R. Markad; R. S. Wagh; M. Neumann; A. A. Kale; V. P. Chimote (Sugar Tech, 2023)

When does temperature matter? Response of rice arsenic to heat exposure during different developmental stages - Yasmine A. Farhat; Soo-Hyung Kim; Rebecca B. Neumann (Plant and Soil, 2023)

Cantharidin increases the force of contraction and protein phosphorylation in isolated human atria - R. Schwarz; B. Hofmann; U. Gergs; J. Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Cantharidin, an inhibitor of protein phosphatase 1 (PP1) and protein phosphatase 2A (PP2A), is known to increase the force of contraction and shorten the time to relaxation in human ventricular preparations. We hypothesized that cantharidin has similar positive inotropic effects in human right atrial appendage (RAA) preparations. RAA were obtained during bypass surgery performed on human patients. These trabeculae were mounted in organ baths and electrically stimulated at 1 Hz. For comparison, we studied isolated electrically stimulated left atrial (LA) preparations and isolated spontaneously beating right atrial (RA) preparations from wild-type mice. Cumulatively applied (starting at 10 to 30 µM), cantharidin exerted a positive concentration-dependent inotropic effect that plateaued at 300 µM in the RAA, LA, and RA preparations. This positive inotropic effect was accompanied by a shortening of the time to relaxation in human atrial preparations (HAPs). Notably, cantharidin did not alter the beating rate in the RA preparations. Furthermore, cantharidin (100 µM) increased the phosphorylation state of phospholamban and the inhibitory subunit of troponin I in RAA preparations, which may account for the faster relaxation observed. The generated data indicate that PP1 and/or PP2A play a functional role in human atrial contractility.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Meteorological influences on airborne pollen and spores in Johannesburg (Gauteng), South Africa - Linus B. Ajikah; Sarah J. Roffe; Frank H. Neumann; Marion K. Bamford; Nanike Esterhuizen; Dilys Berman; Jonny Peter (Aerobiologia, 2023)
Airborne fungal spores and pollen (aerospora), synergistic with air pollution, are key triggers of allergic respiratory diseases. Effective diagnosis and treatment requires up-to-date location-specific knowledge on the temporal variability of aerospora types and levels. Johannesburg is the largest city in South Africa and has grown substantially in three decades, with changes in ground cover, population density and air pollution, yet until now, no continuous aerospora sampling has occurred. We present a daily two-year (August 2019–July 2021) aerospora assemblage for Johannesburg and explore temporal characteristics of 13 dominant aerospora in relation to daily meteorological variables (pressure, rainfall, relative humidity, temperature and wind characteristics). February–July, July–September and January-July represent high-risk periods for fungal spores [( Alternaria alternata (Fries. ex Keissler), Ascospores, Aspergillus niger (Van Tieghem) , Penicillium chrysogenum (Thom), Cladosporium graminum (Corda), Epicoccum nigrum (Link), Helminthosporium solani (Durieu and Montagne) Nigrospora sphaerica (Saccardo ex. Mason), Smuts Ustilago nuda ( Jensen ex. Rostrup) and Torula herbarum (Link)], trees ( Cupressus , Morus and Platanus ) and grass (Poaceae), respectively. Using a generalised additive model, results show that daily meteorological characteristics explained 7–32% of daily aerospora variability, with the largest effect on tree pollen. Rainfall, relative humidity and temperature influenced daily fungal spore and Poaceae counts, with moderate/low rainfall (

Sex-dependent associations of plasma high-density lipoprotein cholesterol and mortality risk in healthy older men and women: two prospective cohort studies - Sultana Monira Hussain; Andrew M Tonkin; Gerald F Watts; Paul Lacaze; Chenglong Yu; Lawrence J Beilin; Zhen Zhou; Anne B Newman; Johannes T Neumann; Cammie Tran; John J McNeil (GeroScience, 2023)
The relationship between high plasma high-density lipoprotein cholesterol (HDL-C) and cause and mortality are not well established in healthy older people. This study examined the associations between HDL-C levels and mortality in initially healthy older men and women. This analysis included participants from the Aspirin in Reducing Events in the Elderly (ASPREE; n =18,668) trial and a matched cohort from the UK Biobank (UKB; n =62,849 ≥65 years). Cox regression was used to examine hazard ratios between HDL-C categories <1.03 mmol/L, 1.03–1.55 mmol/L (referent category), 1.55–2.07 mmol/L, and >2.07 mmol/L and all-cause, cancer, cardiovascular disease (CVD), and “non-cancer non-CVD” mortality. Genetic contributions were assessed using a polygenic score for HDL-C. Among ASPREE participants (aged 75±5 years), 1836 deaths occurred over a mean follow-up of 6.3±1.8 years. In men, the highest category of HDL-C levels was associated with increased risk of all-cause (HR 1.60, 95% CI 1.26–2.03), cancer (HR 1.37, 95% CI 0.96–2.00), and “non-cancer non-CVD” mortality (HR 2.35, 95% CI 1.41–3.42) but not CVD mortality (HR 1.08, 95% CI 0.60–1.94). The associations were replicated among UKB participants (aged 66.9±1.5 years), including 8739 deaths over a mean follow-up of 12.7±0.8 years. There was a non-linear association between HDL-C levels and all-cause and cause-specific mortality. The association between HDL-C levels and mortality was unrelated to variations in the HDL-C polygenic score. No significant association was found between HDL-C levels and mortality in women. Higher HDL-C levels are associated with increased risk from cancer and “non-cancer non-CVD” mortality in healthy older men but no such relationship was observed in women.

Urinary concentrations of metals before and after volcanic eruption: a natural experiment surrounding the eruption of Volcán de Fuego, 2018 - Natalie R. Neumann; Jaime Butler-Dawson; Lyndsay Krisher; Diana Jaramillo; Daniel Pilloni; Greg Waite; Yaqiang Li; Stephen B. Wittels; Kathrin Schilling; Lee S. Newman; Katherine A. James (Environmental Geochemistry and Health, 2023)

A peridotite source for strongly alkalic ultrabasic HIMU lavas of the Oslo Rift, Norway - Eugenia Hyung; Fatemeh Sedaghatpour; Bjørn T. Larsen; Else-Ragnhild Neumann; Zachary T. Eriksen; Michail I. Petaev; Stein B. Jacobsen (Chemical Geology, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The Journal of Medical Toxicology: Our Once and Future Journal - Howard A. Greller; Peter R. Chai; Natalie R. Neumann; Mark B. Mycyk (Journal of Medical Toxicology, 2022)

Effects of acute ischemia and hypoxia in young and adult calsequestrin (CSQ2) knock-out and wild-type mice - Joachim Neumann; Konrad Bödicker; Igor B. Buchwalow; Constanze Schmidbaur; Gustavo Ramos; Stefan Frantz; Ulrich Hofmann; Ulrich Gergs (Molecular and Cellular Biochemistry, 2022)
Calsequestrin (CSQ2) is the main Ca 2+ -binding protein in the sarcoplasmic reticulum of the mammalian heart. In order to understand the function of calsequestrin better, we compared two age groups (young: 4–5 months of age versus adult: 18 months of age) of CSQ2 knock-out mice (CSQ2(−/−)) and littermate wild-type mice (CSQ2(+/+)). Using echocardiography, in adult mice, the basal left ventricular ejection fraction and the spontaneous beating rate were lower in CSQ2(−/−) compared to CSQ2(+/+). The increase in ejection fraction by β-adrenergic stimulation (intraperitoneal injection of isoproterenol) was lower in adult CSQ2(−/−) versus adult CSQ2(+/+). After hypoxia in vitro (isolated atrial preparations) by gassing the organ bath buffer with 95% N 2 , force of contraction in electrically driven left atria increased to lower values in young CSQ2(−/−) than in young CSQ2(+/+). In addition, after global ischemia and reperfusion (buffer-perfused hearts according to Langendorff; 20-min ischemia and 15-min reperfusion), the rate of tension development was higher in young CSQ2(−/−) compared to young CSQ2(+/+). Finally, we evaluated signs of inflammation (immune cells, autoantibodies, and fibrosis). However, whereas no immunological alterations were found between all investigated groups, pronounced fibrosis was found in the ventricles of adult CSQ2(−/−) compared to all other groups. We suggest that in young mice, CSQ2 is important for cardiac performance especially in isolated cardiac preparations under conditions of impaired oxygen supply, but with differences between atrium and ventricle. Lack of CSQ2 leads age dependently to fibrosis and depressed cardiac performance in echocardiographic studies.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

New phylogenetic insights into the African catfish families Mochokidae and Austroglanididae - Frederic D. B. Schedel; Albert Chakona; Brian L. Sidlauskas; Michael O. Popoola; Nadine Usimesa Wingi; Dirk Neumann; Emmanuel J. W. M. N. Vreven; Ulrich K. Schliewen (Journal of Fish Biology, 2022)
Several hundred catfish species (order: Siluriformes) belonging to 11 families inhabit Africa, of which at least six families are endemic to the continent. Although four of those families are well‐known to belong to the ‘Big‐Africa clade’, no previous study has addressed the phylogenetic placement of the endemic African catfish family Austroglanididae in a comprehensive framework with molecular data. Furthermore, interrelationships within the ‘Big‐Africa clade’, including the most diverse family Mochokidae, remain unclear. This study was therefore designed to help reconstruct inter‐ and intrarelationships of all currently valid mochokid genera, to infer their position within the ‘Big Africa clade’ and to establish a first molecular phylogenetic hypothesis of the relationships of the enigmatic Austroglanididae within the Siluriformes. We assembled a comprehensive mitogenomic dataset comprising all protein coding genes and representing almost all recognized catfish families ( N = 33 of 39) with carefully selected species ( N = 239). We recovered the monophyly of the previously identified multifamily clades ‘Big Asia’ and ‘Big Africa’ and determined Austroglanididae to be closely related to Pangasiidae, Ictaluroidea and Ariidae. Mochokidae was recovered as the sister group to a clade encompassing Auchenoglanididae, Claroteidae, Malapteruridae and the African Schilbeidae, albeit with low statistical support. The two mochokid subfamilies Mochokinae and Chiloglanidinae as well as the chiloglanid tribe Atopochilini were recovered as reciprocally monophyletic. The genus Acanthocleithron forms the sister group of all remaining Mochokinae, although with low support. The genus Atopodontus is the sister group of all remaining Atopochilini. In contrast to morphological reconstructions, the monophyly of the genus Chiloglanis was strongly supported in our analysis, with Chiloglanis macropterus nested within a Chiloglanis sublineage encompassing only other taxa from the Congo drainage. This is an important result because the phylogenetic relationships of C. macropterus have been controversial in the past, and because we and other researchers assumed that this species would be resolved as sister to most or all other members of Chiloglanis . The apparent paraphyly of Synodontis with respect to Microsynodontis provided an additional surprise, with Synodontis punu turning out to be the sister group of the latter genus.

Correction to: Coastal flood risk within a peri‑urban area: Sussex Inlet district, SE Australia - E. F. Asbridge; D. Low Choy; B. Mackey; S. Serrao-Neumann; P. Taygfeld; K. Rogers (Natural Hazards, 2022)

Impacts of The Wetland Sedge Carex aquatilis on Microbial Community and Methane Metabolisms - Nicholas B. Waldo; Ludmila Chistoserdova; Dehong Hu; Heidi L. Gough; Rebecca B. Neumann (Plant and Soil, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Coastal flood risk within a peri-urban area: Sussex Inlet district, SE Australia - E. F. Asbridge; D. Low Choy; B. Mackey; S. Serrao-Neumann; P. Taygfeld; K. Rogers (Natural Hazards, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: the importance of private collections - Carolin Haug; Jelle W. F. Reumer; Joachim T. Haug; Antonio Arillo; Denis Audo; Dany Azar; Viktor Baranov; Rolf Beutel; Sylvain Charbonnier; Rodney Feldmann; Christian Foth; René H. B. Fraaije; et al. (PalZ, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Medical Toxicology and COVID-19: Our Role in a Pandemic - Natalie R. Neumann; Peter R. Chai; David M. Wood; Howard A. Greller; Mark B. Mycyk (Journal of Medical Toxicology, 2020)

Stochastic 3D Modeling of Three-Phase Microstructures for Predicting Transport Properties: A Case Study - M. Neumann; B. Abdallah; L. Holzer; F. Willot; V. Schmidt (Transport in Porous Media, 2019)

Contrasting arsenic cycling in strongly and weakly stratified contaminated lakes: Evidence for temperature control on sediment–water arsenic fluxes - P. M. Barrett; E. A. Hull; K. Burkart; O. Hargrave; J. McLean; V. F. Taylor; B. P. Jackson; J. E. Gawel; R. B. Neumann (Limnology and Oceanography, 2019)
Arsenic contamination of lakebed sediments is widespread due to a range of human activities, including herbicide application, waste disposal, mining, and smelter operations. The threat to aquatic ecosystems and human health is dependent on the degree of mobilization from sediments into overlying water columns and exposure of aquatic organisms. We undertook a mechanistic investigation of arsenic cycling in two impacted lakes within the Puget Sound region, a shallow weakly stratified lake and a deep seasonally stratified lake, with similar levels of lakebed arsenic contamination. We found that the processes that cycle arsenic between sediments and the water column differed greatly in shallow and deep lakes. In the shallow lake, seasonal temperature increases at the lakebed surface resulted in high porewater arsenic concentrations that drove larger diffusive fluxes of arsenic across the sediment–water interface compared to the deep, stratified lake where the lakebed remained ~10°C cooler. Plankton in the shallow lake accumulated up to an order of magnitude more arsenic than plankton in the deep lake due to elevated aqueous arsenic concentrations in oxygenated waters and low phosphate : arsenate ratios in the shallow lake. As a result, strong arsenic mobilization from sediments in the shallow lake was countered by large arsenic sedimentation rates out of the water column driven by plankton settling.

Effects of ketamine on brain function during response inhibition - M. Steffens; C. Neumann; A.-M. Kasparbauer; B. Becker; B. Weber; M. A. Mehta; R. Hurlemann; U. Ettinger (Psychopharmacology, 2018)

Correction to: Diel plant water use and competitive soil cation exchange interact to enhance NH4+ and K+ availability in the rhizosphere - Javier F. Espeleta; Zoe G. Cardon; K. Ulrich Mayer; Rebecca B. Neumann (Plant and Soil, 2018)

Correction to: Valuing deaths or years of life lost? Economic benefits of avoided mortality from early heat warning systems - Aline Chiabai; Joseph V. Spadaro; Marc B. Neumann (Mitigation and Adaptation Strategies for Global Change, 2018)

Valuing deaths or years of life lost? Economic benefits of avoided mortality from early heat warning systems - Aline Chiabai; Joseph V. Spadaro; Marc B. Neumann (Mitigation and Adaptation Strategies for Global Change, 2018)

Successful overexpression of wild-type inhibitor-2 of PP1 in cardiovascular cells - Thorsten Krause; Stefanie Grote-Wessels; Felix Balzer; Peter Boknik; Ulrich Gergs; Uwe Kirchhefer; Igor B. Buchwalow; Frank U. Müller; Wilhelm Schmitz; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Diel plant water use and competitive soil cation exchange interact to enhance NH4 + and K+ availability in the rhizosphere - Javier F. Espeleta; Zoe G. Cardon; K. Ulrich Mayer; Rebecca B. Neumann (Plant and Soil, 2017)

Significant implications of permafrost thawing for climate change control - Mikel González-Eguino; Marc B. Neumann (Climatic Change, 2016)

Benefits of greenhouse gas mitigation on the supply, management, and use of water resources in the United States - K. Strzepek; J. Neumann; J. Smith; J. Martinich; B. Boehlert; M. Hejazi; J. Henderson; C. Wobus; R. Jones; K. Calvin; D. Johnson; E. Monier; et al. (Climatic Change, 2015)

Climate change risks to US infrastructure: impacts on roads, bridges, coastal development, and urban drainage - James E. Neumann; Jason Price; Paul Chinowsky; Leonard Wright; Lindsay Ludwig; Richard Streeter; Russell Jones; Joel B. Smith; William Perkins; Lesley Jantarasami; Jeremy Martinich (Climatic Change, 2015)

Genome wide association mapping to identify aluminium tolerance loci in bread wheat - S. Navakode; K. Neumann; B. Kobiljski; U. Lohwasser; A. Börner (Euphytica, 2014)

Improving cross-sectoral climate change adaptation for coastal settlements: insights from South East Queensland, Australia - S. Serrao-Neumann; F. Crick; B. Harman; M. Sano; O. Sahin; R. van Staden; G. Schuch; S. Baum; D. Low Choy (Regional Environmental Change, 2014)

The production and turnover of extramatrical mycelium of ectomycorrhizal fungi in forest soils: role in carbon cycling - A. Ekblad; H. Wallander; D. L. Godbold; C. Cruz; D. Johnson; P. Baldrian; R. G. Björk; D. Epron; B. Kieliszewska-Rokicka; R. Kjøller; H. Kraigher; E. Matzner; et al. (Plant and Soil, 2013)

An association mapping analysis of dormancy and pre-harvest sprouting in wheat - M. A. Rehman Arif; K. Neumann; M. Nagel; B. Kobiljski; U. Lohwasser; A. Börner (Euphytica, 2012)

Genetic studies of seed longevity in hexaploid wheat using segregation and association mapping approaches - M. A. Rehman Arif; M. Nagel; K. Neumann; B. Kobiljski; U. Lohwasser; A. Börner (Euphytica, 2012)

On the presence of serotonin in mammalian cardiomyocytes - Klaus Pönicke; Ulrich Gergs; Igor B. Buchwalow; Steffen Hauptmann; Joachim Neumann (Molecular and Cellular Biochemistry, 2012)

The ectoparasitic mite Tropilaelaps mercedesae (Acari, Laelapidae) as a vector of honeybee viruses - B. Dainat; T. Ken; H. Berthoud; P. Neumann (Insectes Sociaux, 2009)

Pollution-Affected Fish Hepatic Transcriptome and Its Expression Patterns on Exposure to Cadmium - M. Auslander; Y. Yudkovski; V. Chalifa-Caspi; B. Herut; R. Ophir; R. Reinhardt; P. M. Neumann; M. Tom (Marine Biotechnology, 2008)

The phenolic compounds in Cladonia lichens are not antimicrobial in soils - Sari Stark; Minna-Maarit Kytöviita; Antje B. Neumann (Oecologia, 2007)

Human bocavirus DNA detected by quantitative real-time PCR in two children hospitalized for lower respiratory tract infection - T. Schenk; B. Huck; J. Forster; R. Berner; D. Neumann-Haefelin; V. Falcone (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Regional products for the Baltic Sea using MERIS data - H. Krawczyk; A. Neumann; B. Gerasch; T. Walzel (International Journal of Remote Sensing, 2007)

Cells of Pseudomonas putida and Enterobacter sp. adapt to toxic organic compounds by increasing their size - Grit Neumann; Y. Veeranagouda; T. B. Karegoudar; zlem Sahin; Ines Musezahl; Nadja Kabelitz; Uwe Kappelmeyer; Hermann J. Heipieper (Extremophiles, 2005)

Genetic variance of mating frequency in the honeybee (Apis mellifera L.) - F. B. Kraus; P. Neumann; R. F. A. Moritz (Insectes Sociaux, 2005)

RGD-mutants of B-lymphotropic polyomavirus capsids specifically bind to ?v?3 integrin - J. Langner; B. Neumann; S. L. Goodman; M. Pawlita (Archives of Virology, 2004)

Sperm limitation and the evolution of extreme polyandry in honeybees (Apis mellifera L.) - F. B. Kraus; P. Neumann; J. van Praagh; R. F. A. Moritz (Behavioral Ecology and Sociobiology, 2004)

Photo‐identification of short‐beaked common dolphins (Delphinus delphis) in north‐east New Zealand: A photo‐catalogue of recognisable individuals - Dirk R. Neumann; Alexandra Leitenberger; Mark B. Orams (New Zealand Journal of Marine and Freshwater Research, 2002)
Photo‐identification has been established as a helpful tool in cetacean research. However, no study to date has attempted to apply this method to short‐beaked common dolphins (Delphinus delphis L.). We present here the results of two studies that were conducted concurrently in Mercury Bay and the Hauraki Gulf on the north‐east coast of New Zealand's North Island. Methods for distinguishing between individual dolphins are discussed. Sighting records of recognisable individuals indicate that some common dolphins move between Mercury Bay and the Hauraki Gulf (100 km distance), as well as between Mercury Bay and Whakatane (200 km distance). Common dolphin abundance and site fidelity appeared to be greater in the Hauraki Gulf than in Mercury Bay. A selection of photographs of distinct individuals is presented to allow future studies to compare their sighting records to ours, which may help establish the extent of home ranges, site fidelity, and possibly even longevity for common dolphins.

Somatic embryogenesis and DNA organization of genomes from selected Daucus species - J. Imani; L. Tran Thi; G. Langen; B. Arnholdt-Schmitt; S. Roy; C. Lein; A. Kumar; K.-H. Neumann (Plant Cell Reports, 2001)

Characterization of a Series of Far Red Absorbing Perylene Diones: A New Class of Fluorescent Probes for Biological Applications - Nectarios Klonis; Huiqin Wang; Nurul H. Quazi; Joanne L. Casey; Gregory M. Neumann; Dean R. Hewish; Andrew B. Hughes; Les W. Deady; Leann Tilley (Journal of Fluorescence, 2001)

Characterization of a novel 21-kb deletion, CFTRdele2,3(21 kb), in the CFTR gene: a cystic fibrosis mutation of Slavic origin common in Central and East Europe - T. Dörk; M. Macek Jr; F. Mekus; B. Tümmler; J. Tzountzouris; T. Casals; A. Krebsová; M. Koudová; I. Sakmaryová; M. Macek Sr; V. Vávrová; D. Zemková; et al. (Human Genetics, 2000)

On the contractile function of protein phosphatases in isolated human coronary arteries - J. Knapp; P. Bokník; M.C. Deng; S. Huke; I. Lüss; O. Klein-Wiele; B. Linck; H. Lüss; F.U. Müller; P. Nacke; H.H. Scheld; W. Schmitz; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

Inositol-1,4,5-trisphosphate increase by diadenosine tetraphosphate in preparations from failing human myocardium - J. Knapp; P. Bokník; B. Linck; S. Läer; F.U. Müller; J. Neumann; U. Vahlensieck; H. Schlüter; W. Zidek; W. Schmitz (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

The Bereznjakovskoje gold trend, southern Urals, Russia - B. Lehmann; J. Heinhorst; U. Hein; M. Neumann; J. D. Weisser; V. Fedesejev (Mineralium Deposita, 1999)

Interface between haustoria of parasitic members of the Scrophulariaceae and their hosts: A histochemical and immunocytochemical approach - U. Neumann; B. Vian; H. C. Weber; G. Sall (Protoplasma, 1999)

Growth and reproductive cycle of the zebra mussel in the River Rhine as studied in a river bypass - B. Jantz; D. Neumann (Oecologia, 1998)

Phosphate induced carboxylate and proton release by tomato roots - Patricia Imas; B. Bar-Yosef; U. Kafkafi; Ruth Ganmore-Neumann (Plant and Soil, 1997)

Release of carboxylic anions and protons by tomato roots in response to ammonium nitrate ratio and pH in nutrient solution - Patricia Imas; B. Bar-Yosef; U. Kafkafi; Ruth Ganmore-Neumann (Plant and Soil, 1997)

Estimation of exposure of man to substances reacting covalently with macromolecules - P. B. Farmer; H. -G. Neumann; D. Henschler (Archives of Toxicology, 1987)

A clonal analysis of Neisseria meningitidis serogroup A - B. A. Crowe; T. Olyhoek; B. Neumann; B. Wall; M. Hassan-King; B. Greenwood; M. Achtman (Antonie van Leeuwenhoek, 1987)